2017
DOI: 10.1017/s002531541700145x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in the fatty acid composition of ovigerous females and embryos of the squat lobsterPleuroncodes monodon(Decapoda, Munididae)

Abstract: Pleuroncodes monodon, an important fishery resource and key species in the Humboldt Current Large Marine ecosystem, has a prolonged reproductive period from winter until end of summer, and during this time females incubating their embryos are exposed to seasonal variation in food availability and in temperature. Additionally, in order to ensure successful reproduction and survival of embryos, changes occur in the main internal reserves and/or sources of energy of P. monodon. The aim of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…As these larval traits are influenced by the female's energetic investment, they may also be affected by the biochemical condition of the females. Along these lines, studies have shown that female mollusks have higher protein and lipid contents in their hepatopancreas in winter than in summer; a potential adaptive response to provide larvae with higher energetic reserves during periods of low food availability (Bascur, Guzmán, Mora, Espinoza, & Urzúa, ; Calado & Leal, ).…”
Section: Discussionmentioning
confidence: 99%
“…As these larval traits are influenced by the female's energetic investment, they may also be affected by the biochemical condition of the females. Along these lines, studies have shown that female mollusks have higher protein and lipid contents in their hepatopancreas in winter than in summer; a potential adaptive response to provide larvae with higher energetic reserves during periods of low food availability (Bascur, Guzmán, Mora, Espinoza, & Urzúa, ; Calado & Leal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids composition. The composition of fatty acids was determined in 80 samples (20 individuals per study site) using standard methods [40,41]. Fatty acid methyl esters PLOS ONE (FAMEs) were measured after preparation using the lipid extract of samples (lipid content).…”
Section: Plos Onementioning
confidence: 99%
“…For instance, eicosapentaenoic (EPA, 20: 5ω3) and docosahexaenoic (DHA, 22: 6ω3) acids are highly unsaturated fatty acids, which are essential for organisms living at high latitudes (i.e., at low temperatures) because these fatty acids maintain fluidity and the optimal functioning of membranes [ 31 , 39 ]. In this regard, spatial variations in environmental parameters, such as temperature or food availability, can cause differences in the amount and concentration of several fatty acids [ 27 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In P . monodon , seasonal changes in environmental conditions are known to not only affect life history traits [ 56 ], but also the biochemical composition of adult specimens [ 26 , 27 , 48 ]. For instance, in cooler periods, adult individuals have higher biomass than during warmer periods [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation